2021
DOI: 10.1021/acs.inorgchem.1c01922
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Metal Complexes Supported by a Tripodal Tris(amido) Ligand System Featuring an Arene Anchor

Abstract: A new tripodal tris­(amido) ligand system featuring an arene anchor was developed and applied to the coordination chemistry of rare earth metals. Two tris­(amido) ligands with a 1,3,5-triphenylbenzene backbone were prepared in two steps from commercially available reagents on a gram scale. Salt metathesis and alkane elimination reactions were exploited to prepare mononuclear rare earth metal complexes in moderate to good yields. For salt metathesis reactions, while metal tribromides yielded neutral metal tris­… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…4 Å), in contrast to those in the arene-based tripodal tris(amido), tris(phenoxyl) and tris(siloxide) complexes bearing notable Ln–arene bonding interactions. 41,44,45 Gradually decreasing Ln( iii )–O Si bond lengths from 2.228 Å in 1 to 2.066 Å in 5 were observed—as expected according to the ionic radii of Ln( iii ) (for CN = 6, Ce 3+ : 1.01 Å, Lu 3+ : 0.861 Å). 46 The Ln( iii )–O Si bond lengths were found to be comparable to those in the previously reported triphenylsiloxide complexes, such as [(Ph 3 SiO) 3 Ce(THF) 3 ](THF) (2.222(4) Å), 47 [Ph 3 SiO] 6 Y 2 (2.058 (5) and 2.062 (5) Å), 48 and [Ph 3 SiO] 6 Ce 2 (2.185 (6) and 2.141(7) Å).…”
supporting
confidence: 63%
“…4 Å), in contrast to those in the arene-based tripodal tris(amido), tris(phenoxyl) and tris(siloxide) complexes bearing notable Ln–arene bonding interactions. 41,44,45 Gradually decreasing Ln( iii )–O Si bond lengths from 2.228 Å in 1 to 2.066 Å in 5 were observed—as expected according to the ionic radii of Ln( iii ) (for CN = 6, Ce 3+ : 1.01 Å, Lu 3+ : 0.861 Å). 46 The Ln( iii )–O Si bond lengths were found to be comparable to those in the previously reported triphenylsiloxide complexes, such as [(Ph 3 SiO) 3 Ce(THF) 3 ](THF) (2.222(4) Å), 47 [Ph 3 SiO] 6 Y 2 (2.058 (5) and 2.062 (5) Å), 48 and [Ph 3 SiO] 6 Ce 2 (2.185 (6) and 2.141(7) Å).…”
supporting
confidence: 63%
“…It is noteworthy that on one occasion during the synthesis of 3-U, we observed several crystals of the U(IV) complex [U{tacn(SiMe 2 NC 6 H 4 Me-4) 3 }(I)] ( 5), which we attribute to the presence of traces of UI 4 , but the low yield precluded solution phase characterization (see below). Instead of optimizing conditions for the synthesis of 5, we decided to target analogous U(IV) chloride complexes, as straightforward salt metathesis routes to [U{tacn(SiMe 2 NPh) 3 }(Cl)] have been reported previously [10]. By adapting these procedures, the separate reactions of UCl 4 [25,26] with 1-K 3 and 2-K 3 gave the U(IV) complexes [U{tacn(SiMe 2 NC 6 H 4 Me-4) 3 }(Cl)] ( 6) and [U{tacn(SiMe 2 NC 6 H 3 Me 2 -3,5) 3 }(Cl)] (7) in poor yields, following work-up and recrystallization from THF or DME, respectively (Scheme 2).…”
Section: Synthesismentioning
confidence: 99%
“…Inorganics 2021, 9, 86 2 of 15 Over the last 25 years, the tripodal ligands that have proved most popular for generating landmark uranium complexes include the anchored tris-aryloxides {N(CH 2 OAr) 3 } (Ar = substituted aryl), {tacn(CH 2 OAr) 3 } (tacn = 1,3,7-triazacyclononane) and {Mes(CH 2 OAr) 3 } (Mes = C 6 H 2 Me 3 -2,4,6); and the tris-amides {N(CH 2 CH 2 NSiR 3 ) 3 } (SiR 3 = SiMe 3 , Si t BuMe 2, Si i Pr 3 ) [3][4][5][6][7]. Several related macrocyclic ligand systems have more recently been applied in f-element chemistry [8][9][10]. f-Element complexes of tripodal ligands that impose approximate C 3 symmetry have been applied in the electrocatalytic reduction of water [11][12][13], and it has been shown that the steric and electronic effects of substituents on donor atoms of these ligands are crucial for dictating the physicochemical properties of resultant complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The representation of the LUMO of 1Th in Figure a is comprised of 40% metal and 60% arene π*, while that for 1U in Figure b is comprised of 53% metal and 47% arene π*. The presence of δ-symmetry interactions in the LUMOs of 1Th and 1U is reminiscent of the rare-earth complexes bearing an arene-anchored tris­(amido) ligand recently reported by Huang . However, the LUMOs of 1Th and 1U have much larger metal components.…”
Section: Resultsmentioning
confidence: 75%
“…The presence of δ-symmetry interactions in the LUMOs of 1Th and 1U is reminiscent of the rare-earth complexes bearing an arene-anchored tris(amido) ligand recently reported by Huang. 36 However, the LUMOs of 1Th and 1U have much larger metal components.…”
Section: ■ Resultsmentioning
confidence: 99%